“He gives me everything all the time, and I feel bad that I can’t even throw him the ball” : Relational care agency in interspecies care work - Huopalainen, Astrid; Satama, Suvi (Sage, 2026)
What might we learn about care and agency by attuning to the sensory dynamics of human-canine care collaborations? While most research on care focuses on humans, this paper extends the relational care work debate by engaging with interspecies care, foregrounding the nuanced relational care agency that entails nonhuman animal–human interdependency. Drawing on relational and interspecies care literature affording agency to nonhuman animals, we studied 13 assistance dog teams to explore how care is co-created between disabled humans and educated, yet vulnerable, animal workers. The empirical material includes ethnographic observations, interviews with human clients, and photographs. Our findings illustrate often invisible, nonverbal aspects of interspecies care, grounded in mutual trust and the aesthetic “reading” of one another, thereby contributing to a more granular understanding of relational care agency. Second, by showing how dogs, long understood through limited human conceptions, “shift” from care receivers to embodying agential care professionals who disrupt power dynamics and human-centered care norms, we nuance the carer–cared-for relationship in OS. Third, we offer novel insights into interspecies care, encompassing a broader range of animal-driven care practices than previous literature recognized. Finally, our study aims to foster more ethical relationships for working animals and humans alike.